USING BUZZWORD TECHNIQUE IN THE TEACHING OF VOCABULARY TO THE SEVENTH GRADE STUDENTS’ OF SMPN 1 TURATEA JENEPONTO REGENCY - Iskandar, Anita Puspita Sari; Nurpahmi, Sitti (ETERNAL (English, Teaching, Learning, and Research Journal), 2016)
The objectives of this research were to find out the effectiveness of using Buzzword Technique in the Teaching of Vocabulary to the Seventh Grade Students’ of SMPN 1 Turatea Jeneponto Regency and to know the students’ interest in using Buzzword. This research employed quasi-experimental design with two group pre-test and post-test design. There were two variables in this research; they were independent variable (Using Buzzword Technique) and dependent variable (Teaching Students’ Vocabulary). The population of this research was the seventh grade students of SMPN 1 Tutarea Jeneponto Regency academic year 2015/2016 which consisted of 103 students. The sample of the research consisted of 40 students which were taken by using Purposive Sampling, 20 students from VII.5 as the experimental class and 20 students from VII.1 as the control class. There were two kinds of instruments in this research, they were test and questionnaire. Test was used in pre-test and post-test, and questionnaire was used to know the interest of the students after conducted the post test. The data indicated that there was a significant difference between the students’ post-test in experimental class and that in control class. The mean score of post-test (80.6) in experimental class was greater than the mean score of post-test (69.2) in control class. The standard deviation of post-test (7.92) in experimental class and the standard deviation of post-test in control class (13,04). From t-test, the researcher found that the value of t-test (3.34) was greater than t-table (2.086) at the level of significance 0.05 with degree of freedom (df) = 38. Based on the finding and discussion of the research, the researcher suggested that Buzzword Technique could be used in teaching students’ vocabulary. So the researcher concluded that using Buzzword Technique was effective and interesting in teaching Vocabulary.